PROSES PERLAKUAN PANAS UNTUK MELURUSKAN MATERIAL H- BEAM DENGAN METODE FIRING - Ompusunggu, Ferdinand Lincoln; Puspawan, Angky; Hestiawan, Hendri (UNIB Press, 2025)
Welded beam is a profile obtained by welding 3 sheets of plate consisting of 2 flange plates and 1 web plate formed into an I-Beam or H-Beam profile. The welding process is carried out with a special SAW welding machine and continued with a straightening process because the heat from the welding causes the welded beam profile to bend or twist. Due to the heat during welding, there is a minimum welded beam size and the minimum plate thickness cannot be straightened again during the straightening process because the melting point of the material exceeds the limit during the welding process. Firing is the process of burning material at a certain temperature with the intention of improving the dimensions of the material. The purpose of this study is to straighten H-Beam steel. In carrying out the firing process using tools and materials such as the Huawei CG1-30 machine, chalk stamps, square rulers, nitrogen and gas and K3 equipment, in carrying out the firing process, checks are carried out using a square ruler and determining the burning point on the H-Beam steel, chalk stamps are used to measure the temperature in the firing process. The firing process has The conclusion of this study is that the heat treatment process (firing) can straighten H-Beam steel using the Huawei CG1-30 machine which has a speed of 50-750 mm/minute.